Seasonal variability of maximum daily rainfall in Campinas, State of São Paulo, Brazil: trends, periodicities, and associated probabilities - doi: 10.4025/actascitechnol.v35i3.16222 - Blain, Gabriel Constantino (Acta Scientiarum. Technology, 2013)
The extreme rainfall events have received especial focus in the climate literature due to their potential for causing soil erosion, runoff and, soil water saturation. Thus, the aims of the study were (i) to evaluate the presence of trends, temporal persistence and periodical components in the seasonal maximum daily rainfall values (Preabs) obtained from the weather station of Campinas, State of São Paulo, Brazil (1890-2012) and, (ii) to verify the possibility of using the General Extreme Value distribution (GEV) for modeling the probability of occurrence of these extreme rainfall events. The spectral analysis carried out on the time-frequency domain has shown no significant periodicity associated with the variance peaks of the time series under analysis. Based on parametric and non parametric methods and also considering the significance levels usually adopted in the scientific literature (10 and 5%), the Preabs values showed no significant climate trend. The results obtained from qualitative and quantitative goodness-of-fit procedures pointed out that a stationary-GEV model, with time-independent parameters, may be used to describe the probabilistic structure of this meteorological variable. Â